New strategies of civil society in China: a case study of the network governance approach - Fulda, Andreas; Li, Yanyan; Song, Qinghua (Taylor & Francis (Routledge), 2012)
Since the turn of the millennium a second generation of Chinese civil society organisations (CSO) have started taking on issues such as rural migrant integration, social service provision, as well as community building. Organisations such as Beijing-based Shining Stone Community Action (SSCA) can be seen as the avant-garde of a second wave of humanistic, community-based CSO which are willing to help improve the strained state-society relationship in the People´s Republic of China (PR China). In order to advance their values and interests civil society practitioners are willing to engage with Chinese government officials. By gaining the trust of First-in-Command (FIC) cadres they manage to introduce ideas such as the principle of subsidiarity, solidarity and reciprocity. Civil society practitioners thereby initiate open-ended processes of communication, consultation and cooperation. Such processes help promote cross-sector collaboration between Chinese civil society organisations and local government agencies. These developments signify an incremental change from government control (guanzhi) to public management (guanli) and to network governance (zhili). As a framework for the case study the authors look at strategies for the establishment of cooperative relations, focusing on steering mechanisms and process factors. In order to further understand the dynamics of cross-sector collaboration they further explore the social capital dimensions of the principle of reciprocity and trust. To evaluate outcomes and impacts of cross-sector collaboration, the authors discuss the ability of collaboration partners to produce tangible results and to innovate. The findings show that successful experiments with cross-sector collaboration not only depend on structural factors but also on the skills and strategies of the individuals and organisations involved.